Are Gastroenterologists Willing to Implement the "Predict, Resect, and Discard" Management Strategy for Diminutive Colorectal Polyps?: Results From a National Survey. Issue 5 (May 2016) - Soudagar, A. Samad; Nguyen, Minh; Bhatia, Arvin; Rastogi, Amit; Gupta, Neil
Abstract : Goals: To determine whether gastroenterologists would be willing to accept the "predict, resect, and discard" strategy for diminutive colorectal polyps and identify potential barriers to implementation in clinical practice. Background: The ASGE recently published a Preservation and Incorporation of Valuable Endoscopic Innovations (PIVI) document on managing diminutive colorectal polyps using the "predict, resect, and discard" strategy. However, there is no data on whether gastroenterologists would accept this paradigm shift. Study: We performed a random survey of gastroenterologists at a national meeting. Awareness of and willingness to adopt the "predict, resect, and discard" practice, reasons for not utilizing it, and whether a financial incentive would be persuasive in implementing the practice were assessed. Results: A total of 105 gastroenterologists were surveyed. Seventy-six (72%) were aware of the PIVI statement and 64 (61%) stated they would be willing to implement this in practice. Medical-legal concerns (85%) and lack of financial incentives (32%) were the 2 most commonly cited barriers to implementation. Greater than 50% of those resistant to performing the service would be willing do so if given a financial incentive, with ∼50% of gastroenterologists who cited an appropriate incentive preferring >75 to do so. Of these, private practice gastroenterologists and those who had financial interest in sending polyps to pathology were the most likely to request this amount. Conclusions: Approximately two-thirds of gastroenterologists are willing to adopt the "predict, resect, and discard" strategy for managing diminutive colon polyps. Medical-legal concerns and lack of financial incentives are the primary barriers to implementation. Abstract : Supplemental Digital Content is available in the text.